Protein bound fucos, protein bound hexose and total calcium in sera of patient with thyroid dysfunction and control - Aitai, W.F.; AL-arrag, N.F; Rajab, T. M. A.; Hassan, H. G. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Protein bound fucose (PBF), protein bound hexose (PBHex), and total calcium T.Ca) were ’determined in sera of (40) hy-p.ertnyroidism , (40) hypothyroidism patients and (40) controL The resultsr vealed a significant decrease in the kwel of PBF, PBHex and T.Ca in sera of patients with .hyperthyroidism compared to control; Inc se Qf PBF. there nQ difference in its level betwe.en patients with hypothyroidism and control group. While there is a significant increment in PBHex leveli:n both hyper and hypothyroidism With respect to that of control Result indicates, that total calcium levels were i.n the nomml range for all p tients groups. Patient compared to control no difference in the level of (PBF) b tween hypoth.yroid1sm and controL A significant increa;;.e in the level of PBHex in sera of hyper and hypothy:roidJsm compared to controlwas found.